Analysis and reflections on special Education in Brazil: the 2021 scenario - Sestito, Camila Dias de Oliveira; Milani, Thiago Giroto [UNESP] (Univ Nove Julho, 2023)
Accessibility issues are being increasingly addressed in legislation and inclusion practices adopted in the country and the world. Regarding education, some approaches were implemented aiming at a more inclusive school environment, such as the Special Education modality. To verify how Special Education is being attended in Brazilian institutions, the present study aimed to analyze open data made available by the National Institute of Educational Studies and Research Anisio Teixeira [Inep] from 2021 to diagnose the status of Special Education in Brazil, through clustering techniques. The results presented new perceptions about the Brazilian Special Education modality, showing regions that need more investment in the educational area, as well as regions with difficulties in the use of technologies, which can cause several problems, such as school dropout.
Keywords: Brazilian education; people with disabilities; technologies in schools